Bridging Digital Divide Among Demographics: Need, Barriers and Ways - Nupur (Gyan Management Journal, 2024)
With the help of service delivery through mobile phones and other electronic  devices using internet, there is a reduction in the fatigue of customers. And this  is a positive note in digitalization of public electronic service delivery system.  But the spread of information and communication technology and digital  transformation across the world has given birth to digital divide especially  in developing and developed countries. The unequal distribution of income,  age disparity, gender differences and differing educational background are  the bases on which the gap is widening. Digital competency is a necessity.  For bridging the gap, no one can afford to be left behind. Present study is an  attempt to understand the need and challenges faced in eliminating digital  divide and the possible ways to handle the problem.
Keywords: Digital divide; sociodemographic; determinants